2013
DOI: 10.1080/17470919.2013.807873
|View full text |Cite
|
Sign up to set email alerts
|

Perspective taking modulates positivity bias in self-appraisals: Behavioral and event-related potential evidence

Abstract: Previous studies have reported that when people self-reflect--they typically judge the self as more positive (or less negative) compared to others on a range of dimensions (such as health, social skills, or achievement). In the present study, we investigated whether viewing the self through the eyes of other people reduces this egocentric (self-centered) bias. Event-related brain potentials (ERPs) were examined in 17 subjects who performed judgments of adjectives in positive or negative valences from either se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 62 publications
5
36
2
Order By: Relevance
“…There was an interaction between self-reference and emotion observed in both the behavioral RT and late LPP in the left anterior brain. The results are generally consistent with the findings in previous studies using an implicit paradigm (Herbert et al, 2011a , b ; Chen et al, 2014 ; Wu et al, 2014 ), but the time courses are later than those with the explicit paradigm (Zhang et al, 2013 ; Zhou et al, 2013 ; Yang et al, 2014a ; Cai et al, 2016 ; Li et al, 2016 ). These patterns indicate that the increased specificity of the self-reference would bring forward the combination of self-reference and emotion information.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…There was an interaction between self-reference and emotion observed in both the behavioral RT and late LPP in the left anterior brain. The results are generally consistent with the findings in previous studies using an implicit paradigm (Herbert et al, 2011a , b ; Chen et al, 2014 ; Wu et al, 2014 ), but the time courses are later than those with the explicit paradigm (Zhang et al, 2013 ; Zhou et al, 2013 ; Yang et al, 2014a ; Cai et al, 2016 ; Li et al, 2016 ). These patterns indicate that the increased specificity of the self-reference would bring forward the combination of self-reference and emotion information.…”
Section: Discussionsupporting
confidence: 90%
“…ERP analysis showed that emotion was rapidly discriminated in an early time window of early posterior negativity (EPN, 200–300 ms), regardless of whether the preceding words were self-referential or other-referential, while emotion was modulated by self-reference in the later stage of LPP (450–600 ms; Herbert et al, 2011b ). The later interaction between self-reference and emotion is consistent with findings in the self-referential emotion task without discrimination of self- and other-relevant (Zhou et al, 2013 ; Cai et al, 2016 ; Li et al, 2016 ) and further suggest that self-reference interacts with emotion to categorize information, but after emotional discrimination. Nevertheless, the self-discrimination effect was not reported.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the symbolic interactionist tradition, the ability to perceive oneself from a third-person perspective is considered integral to the development of the self (Goffman, 1959;Mead, 1934). Indeed, considering oneself from the third-person perspective is linked to future prosocial behavior (Leary, Estrada, & Allen, 2009;Libby, Shaeffer, Eibach, & Slemmer, 2007) and improved perspective taking (Stephenson & Wicklund, 1983;Zhou et al, 2013), eliciting greater activity in brain regions related to emotion and memory (e.g., Ochsner et al, 2005).…”
mentioning
confidence: 99%